Immunologically effective biomaterials-enhanced vaccines against infection of pathogenic microorganisms - Qi Wei; Shixian Liu; Xu Huang; Hua Xin; Jianxun Ding (Elsevier, 2023)
Infectious diseases are severe public health events that threaten global health. Prophylactic vaccines have been considered as the most effective strategy to train the immune system to recognize and clear pathogenic infections. However, the existing vaccines against infectious diseases have several limitations, such as difficulties in mass manufacturing and storage, weak immunogenicity, and low efficiency of available adjuvants. Biomaterials, especially functional polymers, are expected to break through these bottlenecks based on the advantages of biocompatibility, degradability, controlled synthesis, easy modification, precise targeting, and immune modulation, which are excellent carriers and adjuvants of vaccines. This review mainly summarizes the application of immunologically effective polymers-enhanced vaccines against viruses- and bacteria-related infectious diseases and predicted their potential improvements.